(untitled) - Hobza, Pavel (Aither, 2013)
Aristotle is generally seen both as a philosopher and as a scientist. By closely looking, however, he himself does not seem to distinguish between philosophy and science. If we want to find out how he conceives of philosophy and science, it is first necessary to inquire into his conception of episteme. For, from Aristotle's point of view, both philosophy and science should meet the criteria of episteme, one of the most important of which is that it is based upon the first principles. Moreover, the term episteme is usually translated as science. After scrutinizing various possibilities of how Aristotle conceived of episteme (e.g., its threefold division), it is to conclude that despite some similarities and analogies Aristotle did not in fact make any distinction that would resemble our distinction between philosophy and science. Hence, it is misleading to speak of philosophy and science in Aristotle.